Servant leadership in action : how you can achieve great relationships and results - Blanchard, Kenneth H.; Broadwell, Renee (Berrett-Koehler Publishers, Inc., 2018)
"The only way to create great relationships and results is through servant leadership. It's all about putting other people first."--The foreword by John Maxwell We've all seen the negative impact of self-serving leaders in every sector of our society. Not infrequently, they end up bringing down their entire organization. But there is another way: servant leadership. Servant leaders lead by serving their people, not by exalting themselves. This collection features forty-four renowned servant leadership experts and practitioners--prominent business executives, bestselling authors, and respected spiritual leaders--who offer advice and tools for implementing this proven, but for some still radical, leadership model. Edited by legendary business author and lifelong servant leader Ken Blanchard and his longtime editor Renee Broadwell, this is the most comprehensive and wide-ranging guide ever published for what is, in every sense, a better way to lead